The application of the small punch tensile test to evaluate the ductile to brittle transition of a thermally sprayed CoNiCrAlY coating - Jackson, G.A.; Sun, Wei; McCartney, D.G. (Trans Tech Publications, 2017)
Thermally sprayed MCrAlY bond coats are important elements of thermal barrier coating (TBC) systems which are applied to the surface of gas turbine components to protect them in high temperature environments. Knowledge of their mechanical properties is essential in preventing TBC failure which can have catastrophic consequences. However, limited data on modulus, strength and ductility are available for such coatings. In this work, the ductile to brittle transition behaviour of a CoNiCrAlY coating has been investigated via the small punch tensile test (SPTT). Displacement controlled tests were carried out on free standing coatings at room temperature (RT) and between 400-750 °C at a rate of 1 μms-1. At low temperatures there was evidence of elastic-brittle behaviour and at high temperatures there was clear evidence of yielding and plastic deformation. The ductile to brittle transition temperature was found to be between 500-750 °C. The yield stress ranged from 1000-1500 MPa below 600 °C to less than 500 MPa above 650 °C. The elastic modulus was found to be approximately 200-230 GPa at 500 °C and 55 GPa above 700 °C. At room temperature the fracture surface showed flat, smooth features indicating brittle failure whereas at 700 °C there was evidence of ductile tearing.